Indonesia Obligation to Repatriate Nationals Who Had Joined the Islamic State of Iraq and Syria - Hanif Nur Widhiyanti; Mukhlisa Ilman Nafiah Medianto (Fiat Justisia, 2022)
The Montevideo Convention of 1993 establishes that a state must have a defined population, territory, government, the capacity to engage in relations with other states, and recognition of sovereignty. This raises questions about whether ISIS can be classified as a state or a belligerent organization. Although the Islamic State of Iraq and Syria claims to have a population, territory, and governance, it lacks the ability to engage in diplomatic relations. The National Counter-Terrorism Agency (BNPT) has classified ISIS as a radical terrorist movement. Data from BNPT and Detachment 88 indicate that approximately 1,276 Indonesian nationals have joined ISIS, of which around 297 hold Indonesian passports. This situation prompts a debate regarding Indonesia's responsibility for these individuals and their retention of Indonesian nationality. This article presents findings from normative juridical research analyzing Indonesia's obligations to repatriate citizens who have joined ISIS. The research concludes that these individuals qualify as Foreign Terrorist Fighters (FTFs). However, international law does not regulate the nationality status of FTFs, and each state retains the authority to determine its nationality laws. Consequently, the Indonesian government has the responsibility to repatriate its citizens involved with ISIS.